Total bacteriological and coliforms counts in frozen fish fillets in Rio de Janeiro, Brazil - Barros, Glênio Cavalcanti de; Robbs, Paschoal Guimarães (Pesquisa Agropecuaria Brasileira, 2014)
The microbiological quality of frozen fish fillets was studied through the total bacteriological counts in the Greater Rio de Janeiro. Ten different brands of fish fillets were analyzed, in a total of 34 samples. The average results were: a) mesophilic aerobic (30°C): 1.6 x 104 to 2.3 x 107 cells/g; b) psychrophilic aerobic (± 5°C): 5.7 x 104 to 2.4 x 107 cells/g; c) psychrophilic aerobic (± 15°C): 3.5 x 105 to 3.8 x 107 cells/g; d) mesophilic anaerobic (30°C): 9.0 x 104 to 1.7 x 107 cells/g; e) coliforms (M.P.N.): 0 to 230 coliforms/g. It was concluded that the sanitary quality of the frozen fish filets analyzed, is not meeting the standard requirements, in relation to the count per gram of bacteria and to the presence of coliforms.